Inside Back Cover: Selective Hydrogenation of Furfural to Furfuryl Alcohol in the Presence of a Recyclable Cobalt/SBA‐15 Catalyst (ChemSusChem 11/2015). Issue 11 (18th September 2014) - Audemar, Maïté; Ciotonea, Carmen; De Oliveira Vigier, Karine; Royer, Sébastien; Ungureanu, Adrian; Dragoi, Brindusa; Dumitriu, Emil; Jérôme, François
<x xml:space="preserve">Abstract</x> The Inside Back Cover picture shows a recyclable monometallic Co/SBA‐15 being active and selective in the hydrogenation of furfural to furfuryl alcohol and in the hydrogenation of levulinic acid to γ‐valerolactone. A high selectivity to furfuryl alcohol can be achieved, and the catalytic active sites have been determined to be cobalt metallic species. Moreover, this work shows that this catalyst can be active in the hydrogenation of furfural to furfuryl alcohol under solvent‐free conditions. More details can be found in the Full Paper by Audemar et al. (DOI: 10.1002/cssc.201403398).